Digital futures for Europe - Meelis Kitsing (European Centre for International Political Economy (ECIPE), 2021)
There isn't one model for success in the digital future; there are many. Europe is now debating what policies that could help to power entrepreneurship and growth in Europe's economy, and some are arguing that Europe should make itself technologically sovereign - independent from the big platforms from the US. This is not the right approach - partly because there cannot be just one model applied in Europe if it is to become more successful in technology and competitiveness. This briefing paper argues that is far more important for Europe to create a better environment for companies to experiment and discover with new business models, and to learn from the past platform success while they do so. That requires a much greater space for entrepreneurship and that the EU and national governments stay away from excessive regulations that strain new business growth. Europe can be a powerful region that shapes rules and standards globally - "the Brussels effect". But that isn't the future for Europe if it ensnares entrepreneurs in red tape - "the Brussels defect".
Keywords: 330; Digitalisierung; Zukunftsforschung; EU-Staaten